An architectural proposal to protect the privacy of health data stored in the blockchain - Sega, C.; Rossetto, A.; Correia, S.; Valderi Leithardt (Iberian Conference on Information Systems and Technologies, CISTI, 2022)
Blockchain is a public ledger, decentralized and distributed on the peer-to-peer network that uses a block structure to verify and store data, employing a reliable consensus mechanism. With the rapid development of this technology in recent years, several concerns and obstacles to its application in some scenarios began to emerge, among them privacy being one of the topics mentioned in several works. This work proposes an architecture to guarantee the privacy of health data, which are stored within a Blockchain network in a decentralized way, through the use of encryption techniques that will be compared such as RSA (Rivest-Shamir-Adleman) and the ECC (Elliptic Curve Cryptography).